Informing Better Trial Design: A Technical Comment on Lortie-Forgues and Inglis (2019). (May 2020) - Sims, Sam
Lortie-Forgues and Inglis (2019) convincingly demonstrate that 40% of rigorous, large-scale education trials are uninformative about impact. However, they and others dismiss the value of larger trials for solving this problem, based on a miscalculation. Contrary to this, I argue that making trials larger is a feasible and affordable way of making them more informative.